KLEBSIELLA PNEUMONIAE: ASPECTS OF POPULATION GENOMICS - Gisinger, Oksana (Interdisciplinary Approaches to Medicine, 2024)
Klebsiella pneumoniae is one of the causes of antimicrobial-resistant opportunistic infections. Klebsiella pneumoniae is naturally resistant to penicillins and many antimicrobials. Knowledge about the ecology, population structure, or pathogenicity of K. pneumoniae is limited by laboratory technology. K. pneumoniae is a threat for public health due to an increase in healthcare-associated infections caused by multidrug-resistant strains that produce extended-spectrum β-lactamases and/or carbapenemases. The phenomenon of severe community-acquired infections caused by particularly virulent K. pneumoniae is associated with strains expressing acquired virulence factors. The presence of such serious biomedical problems makes sustained interest in research on K. pneumoniae using genetic methods. In this article, we discuss the possibilities of genomic approaches, their role in understanding the taxonomy, ecology, and evolution of K. pneumoniae, its diversity, and the distribution of clinically relevant determinants of pathogenicity and antimicrobial resistance. A detailed consideration of the structure and diversity of the K. pneumoniae population is important for understanding research results, interpreting clinical data, and developing and implementing methods to combat this pathogen. Key words: Klebsiella pneumoniae, antimicrobial-resistant, ecology, population, opportunistic infections, genomics.